THE IMPACT OF GRAIN SIZE AND PROPPANT PLACEMENT ON OPTIMIZATION OF OILWELL HYDRAULIC FRACTURING - EDI NUGROHO (NIM : 22208028), SAPTO
The economic value of hydraulic fracturing treatment determined by postfracturing well performance relative to the cost of treatment employed. Postfracturing well productivity largely defined by the effective fracture area, which is fracture portion that gives sufficient conductivity larger than reservoir to increase flow capacity of reservoir fluid into wellbore. Improving effective fracture area can be achieved by a better proppant placement and increased proppant grain size. The use of perfect support fluid which allow a better suspension in proppant transport process has been widely chosen to ensure a better proppant distribution in fracture, rather than a banking fluid which characterized by a high proppant settling velocity. While use of bigger proppant will increase fracture conductivity affected by bigger proppant pack permeability created. With aid of a pseudo-3D fracture simulator, study employed to compare the use of a different fluid type and proppant size and their effect on effective fracture area resulted for different fracture model of downward height growth. Case study simulation shows that for fracture geometry with downward height growth containment model, the use of banking fluid and bigger proppant give a better economic value with NPV for 1 year period is 1.114.572 US$. In other hand, for a fracture with extensive downward height growth, perfect support fluid with a bigger proppant is still the best choice to maximize fracture economic with NPV of 2.731.607 US$.